The site pair matching of a tandem Au/CuO–CuO nanocatalyst for promoting the selective electrolysis of CO2 to C2 products. Issue 61 (29th November 2021) - Zhou, Jun-Hao; Yuan, Chen-Yue; Zheng, Ya-Li; Yin, Hai-Jing; Yuan, Kun; Sun, Xiao-Chen; Zhang, Ya-Wen
Abstract : C2 product FE of 52.8% was achieved in eCO2 RR at −1.0 V vs. RHE using a nanoporous hollow Au/CuO–CuO tandem catalyst due to the matching of optimal working potentials and charge-transfer resistances of the CO-production sites and CO-reduction sites. Abstract : Tandem catalysis, in which a CO2 -to-C2 process is divided into a CO2 -to-CO/*CO step and a CO/*CO-to-C2 step, is promising for enhancing the C2 product selectivity when using Cu-based electrochemical CO2 reduction catalysts. In this work, a nanoporous hollow Au/CuO–CuO tandem catalyst was used for catalyzing the eCO2 RR, which exhibited a C2 product FE of 52.8% at −1.0 V vs. RHE and a C2 product partial current density of 78.77 mA cm −2 at −1.5 V vs. RHE. In addition, the C2 product FE stably remained at over 40% over a wide potential range, from −1.0 V to −1.5 V. This superior performance was attributed to good matching in terms of the optimal working potential and charge-transfer resistance between CO/*CO-production sites (Au/CuO) and CO/*CO-reduction sites (CuO). This site pair matching effect ensured sufficient supplies of CO/*CO and electrons at CuO sites at the working potentials, thus dramatically enhancing the formation rate of C2 products.